Seven keys to unlock autism : making miracles in the classroom - Hall, Elaine, 1956- (Jossey-Bass, 2012)
This book can help anyone develop a personal skill set to better understand and access these often hard - to reach children. Step - by -step, this engaging book shows how to identity these skills and use them in your daily interaction with kids on the autism spectrum. Using the ideas outlined in the book, teachers and parents can create more meaningfull relationships for optimal results in the classroom and at home.